Comparison of mean duration of diarrhea of two different probiotics in Acute Diarrhea among children - RCT - Ikram, Sikander; Urooj, Rani Saba; Mehak, Noor-Ul-Ain; Omer, Riffat; Tahira, Fatima; Masoud, Adeel; Laique, Talha (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Diarrhea is one of the leading causes of morbidity and mortality and morbidity in paediatric age group. Aim: To determine compare the mean duration of diarrhea in single strain (saccharomyces boulardii) and multiple strain probiotic in acute diarrhea in children. Study Design: Randomized controlled trial. Methodology: The current project was conducted at Department of Pediatrics, General Hospital, Lahore. The patients were randomly categorized in two groups. 5 billion lyophilized heat-killed multiple strain probiotic (Group-B) was given twice a day and 250 mg of saccharomyces boulardii (Group-A) was given twice a day. Data analyzed by using SPSS 15.0. Independent t-test was applied for comparison of mean duration of diarrhea between groups. Results: The mean age of patients were 14.3 ± 4.19 months. The mean duration of diarrhea in Group A was 78.7±13.2 hrs whereas in Group B, mean duration of diarrhea was 97.6 ± 13.6 hrs. Conclusion: Single strain saccharomyces boulardii significantly reduced the mean duration of diarrhea in children.